Consecutive Ring Expansion and Contraction for the Synthesis of 1‐Aryl Tetrahydroisoquinolines and Tetrahydrobenzazepines from Readily Available Heterocyclic Precursors. Issue 20 (17th April 2018) - Hill, Jessica E.; Matlock, Johnathan V.; Lefebvre, Quentin; Cooper, Katie G.; Clayden, Jonathan
Abstract: Tetrahydroisoquinolines and tetrahydrobenzazepines were prepared by acid‐promoted ring contraction of cyclic ureas, which were themselves formed by ring expansion of indolines and tetrahydroquinolines. The consequent overall one‐carbon insertion reaction gives these 6‐ and 7‐membered heterocyclic scaffolds in three steps from readily available precursors. Other ring sizes may be formed by an alternative elimination reaction of bicyclic structures. Scalability of the method was demonstrated by operating it in a flow system. Abstract : More and less : Acid‐induced ring contraction of medium‐ring ureas provides access to valuable bioactive scaffolds such as tetrahydroisoquinolines and tetrahydrobenzazepines. The cyclic ureas are first formed by ring expansion of indolines and tetrahydroquinolines, and the consequent overall one‐carbon insertion reaction gives these 6‐ and 7‐membered heterocyclic scaffolds in three steps from readily available precursors.